Ces hommes qui viennent du social - Guéguen, Jean-Yves
couv. ill. en coul. La couv. porte en plus : "François Chérèque, Patricia Adam, Dominique Fraise, Agnès Guerry, Brigitte Bouquet, Jean-Luc Einaudi, Fabienne Brugel, Vincent Lacote"